„Podróż ku sobie w podróże od siebie”. O poezji i sztuce Ewy Kuryluk - Stankowska, Agata (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The paper is devoted to Ewa Kuryluk’s poetry and art. The author describes intermingling dimensions of the poet’s artistic identity – existential, hermeneutical and aesthetical – presenting three major tensions present in her work. The first one is between the apocalypse and utopia. The second one may be described by the phrase from one of her poems, establishing the first rule of hermeneutics, according to which she tries to understand herself and the world. The poet defines existence and understanding as a “journey towards oneself and from oneself”. The idea of the third tension may be defined as a spread between the shade/contour and the reflection/picture. The author focuses on presenting the parallels between Kuryluk’s artistic work and her early poems.